18F PSMA-1007 and 18F FDG PET/CT in an Advanced Prostate Cancer Patient - A Case Report - Mutsuddy, Pupree; Mandal, Tapati; Akhter, Papia; Rahman, S M Arifur; Siddique, Md Abu Bakker; Begum, Fatima; Zohra, Fatema Tuz; Azim, Mohammad Anwar Ul; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2025)
Positron Emission Tomography (PET) is currently playing a crucial role in the assessment of prostate cancer. 68Ga/18F prostate-specific membrane antigen (PSMA), 11C Choline, and 18F Fluciclovine are the most commonly used non-FDG PET tracers. F-18 FDG PET is not routinely recommended in prostate cancer due to the low glycolytic nature of the prostate tumor cells. However, in advanced and aggressive cases, 18F FDG PET can detect lesions. Till September 2023, 18F-FDG was the only available PET tracer in our country to detect recurrence and non-osseous metastases. We reported a case of a 53-year-old male who underwent an 18F PSMA-1007 PET-CT scan for restaging in October 2023. The patient had a previous 18F FDG PET-CT scan in January 2023. FDG PET showed hypermetabolic cervical, mediastinal, and abdominal lymph nodes as well as multiple skeletal lesions. Patient received chemotherapy and anti-androgen therapy. However, after 10 months, patients PSA raised from 225 ng/ml to 616.5 ng/ml. In the PSMA scan, we found extensive nodal and skeletal involvements with progression of disease. In this case, an FDG-positive scan reflects the aggressiveness of the disease; however, extensive PSMA-avid lesions, including the positive lesions in FDG, indicate the patient could benefit from PSMA-based therapy. Bangladesh J. Nuclear Med. 28(1): 174-177, 2025